Identification of the Rage-dependent gene regulatory network in a mouse model of skin inflammation - Riehl, Astrid; Bauer, Tobias Hartmut; Brors, Benedikt; Busch, Hauke; Mark, Regina; Németh, Julia; Gebhardt, Christoffer; Bierhaus, Angelika; Nawroth, Peter Paul; Eils, Roland; König, Rainer; Angel, Peter; et al. (BMC genomics, 2010)
In the past, molecular mechanisms that drive the initiation of an inflammatory response have been studied intensively. However, corresponding mechanisms that sustain the expression of inflammatory response genes and hence contribute to the establishment of chronic disorders remain poorly understood. Recently, we provided genetic evidence that signaling via the receptor for advanced glycation end products (Rage) drives the strength and maintenance of an inflammatory reaction. In order to decipher the mode of Rage function on gene transcription levels during inflammation, we applied global gene expression profiling on time-resolved samples of mouse back skin, which had been treated with the phorbol ester TPA, a potent inducer of skin inflammation.
Gesehen am 17.05.2023